Recommendations for older adults' physical activity and sedentary behaviour during hospitalisation for an acute medical illness: an international Delphi study - Claire E. Baldwin; Anna C. Phillips; Sarah M. Edney; Lucy K. Lewis (BMC, 2020)
Abstract Background Immobility is major contributor to poor outcomes for older people during hospitalisation with an acute medical illness. Yet currently there is no specific mobility guidance for this population, to facilitate sustainable changes in practice. This study aimed to generate draft physical activity (PA) and sedentary behaviour (SB) recommendations for older adults' during hospitalisation for an acute medical illness. Methods A 4-Round online Delphi consensus survey was conducted. International researchers, medical/nursing/physiotherapy clinicians, academics from national PA/SB guideline development teams, and patients were invited to participate. Round 1 sought responses to open-ended questions. In Rounds 2-3, participants rated the importance of items using a Likert scale (1-9); consensus was defined a priori as: ≥70% of respondents rating an item as "critical" (score ≥ 7) and ≤ 15% of respondents rating an item as "not important" (score ≤ 3). Round 4 invited participants to comment on draft statements derived from responses to Rounds 1-3; Round 4 responses subsequently informed final drafting of recommendations. Results Forty-nine people from nine countries were invited to each Round; response rates were 94, 90, 85 and 81% from Rounds 1-4 respectively. 43 concepts (items) from Rounds 2 and 3 were incorporated into 29 statements under themes of PA, SB, people and organisational factors in Round 4. Examples of the final draft recommendations (being the revised version of statements with highest participant endorsement under each theme) were: "some PA is better than none", "older adults should aim to minimise long periods of uninterrupted SB during waking hours while hospitalised", "when encouraging PA and minimising SB, people should be culturally responsive and mindful of older adults' physical and mental capabilities" and "opportunities for PA and minimising SB should be incorporated into the daily care of older adults with a focus on function, independence and activities of daily living". Conclusions These world-first consensus-based statements from expert and stakeholder consultation provide the starting point for recommendations to address PA and SB for older adults hospitalised with an acute medical illness. Further consultation and evidence review will enable validation of these draft recommendations with examples to improve their specificity and translation to clinical practice.